Handwriting Recognition Using Eccentricity and Metric Feature Extraction Based on K-Nearest Neighbors - Hari Rachmawanto, Eko; Rambu Anarqi, Galang; Moses Setiadi, De Rosal Ignatius; Atika Sari, Christy (2018 International Seminar on Application for Technology of Information and Communication, 2018)
The process of handwriting recognition aims to digitize handwriting without having to retype handwriting. This study proposes the extraction of Eccentricity and roundness features based on K-Nearest Neighbors (KNN) to recognize handwriting. To maximize the process of recognition is done several stages of preprocessing stages such as thresholding, noise filtering, and cropping stage to take every character on handwriting image. Each image that has been through the preprocessing process is further extracted features. Eccentricity and metric are the features of the extracted form of each image to be recognized. After obtained the two features are then carried out the training process to group the feature form on each type of letter. Next, KNN is used to classify each letter character. Based on the results of testing the proposed method for recognition of handwriting characters obtained an accuracy of 85.38%.